Locally Regularized Smoothing B-Snake. (25th February 2007) - Velut Velut, Jérôme Jérôme; Benoit-Cattin Benoit-Cattin, Hugues Hugues; Odet Odet, Christophe Christophe
Abstract : We propose a locally regularized snake based on smoothing-spline filtering. The proposed algorithm associates a regularization process with a force equilibrium scheme leading the snake's deformation. In this algorithm, the regularization is implemented with a smoothing of the deformation forces. The regularization level is controlled through a unique parameter that can vary along the contour. It provides a locally regularized smoothing B-snake that offers a powerful framework to introduce prior knowledge. We illustrate the snake behavior on synthetic and real images, with global and local regularization.